Chemistry - Peter G. Mahaffy (Nelson Education, 2011)
An integrated print/digital resource package that presents Chemistry as an integrated whole, blending as far as possible organic, physical, and inorganic chemistry phenomena with case studies, illustrations and models that enable visualization and critical thinking without compromising scientific rigour